Answer:
x = - 3, x = 2
Step-by-step explanation:
Since x = 1 is a zero then (x - 1) is a factor of the polynomial
dividing x³ - 7x + 6 ÷ (x - 1)
= (x - 1)(x² + x - 6)
= (x - 1)(x + 3)(x - 2)
equating (x + 3)(x - 2) = 0 gives the other zeros
equate each factor to zero and solve for x
x + 3 = 0 ⇒ x = - 3
x - 2 = 0 ⇒ x = 2
–8 > –1
B.
5 < 10
C.
–5 < –2
D.
14 > –9
for #3, 7 out of the eight pieces are shaded... 7/8
Now, we need however many out of 16, so you need to multiply 7 and 8 both by 2, 14/16... so you should shade 14 out of the 16 pieces
Hope this helped!!! :)
Answer:
Step-by-step explanation:
We have been given an expression and we are asked to find the product of our given expression.
Using exponent rule of power to powers we can write as and .
Upon substituting these values in our expression we will get,
Using exponent rule we will get,
Multiplying by we will get,
Using exponent rule we will get,
Therefore, the simplest form of the product of our given expression will be .
Answer:
Step-by-step explanation: